A novel stick-slip based linear actuator using bi-directional motion of micropositioner. (1st August 2019) - Guo, Z.; Tian, Y.; Zhang, D.; Wang, T.; Wu, M.
Highlights: An asymmetric flexure-based mechanism was used to realize bi-directional outputs. A modified sawtooth wave with a cycloid fall curve was used as the driving signal. Various experiments have been implemented on the developed prototype. Abstract: A stick-slip based linear actuator was proposed in this paper, which applied the axial motion of the micropositioner to adjust the preload, and the lateral motion to drive the slider. The bi-directional motion of the micropositioner was realized through the asymmetric structure of a flexure-based mechanism, which includes two right circular flexure hinges and four leaf-spring flexure hinges. The static analysis, kinematic analysis and optimization design were successively implemented on the flexure-based mechanism. The Finite Element Analysis (FEA) proved the flexure-based mechanism could generate the bi-directional motion as designed. A prototype of the linear actuator was developed and the measuring system was constructed. A modified sawtooth wave with a cycloid fall curve was designed to improve the output property. The experimental results showed the modified sawtooth wave generated larger velocity than the traditional sawtooth wave in same driving voltages, fall times, driving frequencies and loads. The amplification coefficient and resolution of the proposed linear actuator in single step were 3.16 and 60 nm, respectively. The maximal velocity was 26.2 mm/s with the modified sawtooth wave in driving frequency of 500 Hz.